Winning 2025 PNW written abstract - Chiang, Cindy (Operating Room Nurses Association of Canada Journal, 2026)
Time has shown that perioperative nurses who embody advocacy, compassion, and surgical excellence can overcome even the most challenging barriers. Perioperative nurses work not only behind masks and within restricted areas, but also behind the scenes, collaborating with the patient and surgical team to ensure safety throughout every phase, from preoperative to postoperative care.